Reconfiguring livestock value chains for climate resilience: circular and nature-based transitions through transdisciplinary governance - Neogi, Sucharit Basu (Asian-Australasian Journal of Food Safety and Security, 2026)
Abstract not available Asian Australas. J. Food Saf. Secur. 2026, 10(1), 1-5